Fecal microbiota transplantation alleviates weaning stress in Tibetan piglets by modulating gut microbiota–metabolite interactions - Zhang, Jian; Zhao, Mingxuan; Zhang, Hongliang; Han, Mengjia; Tan, Zhankun; Shang, Peng (Frontiers in Animal Science, 2025)
Weaned piglets are highly stress-vulnerable, with reduced immunity. Conventional use of antibiotics to prevent diarrhea and boost growth carries risks: bacterial resistance, drug residues, and intestinal flora imbalance, threatening food safety and public health. Meanwhile, demand for antibiotic-free livestock products is rising. Many countries have adopted policies restricting or banning antibiotics. Thus, developing safe, effective antibiotic alternatives is vital—to ensure piglet health, align with the industry’s green development, and meet market needs. This study experiment used a fecal microbiota transplantation method on weaned piglets and systematically evaluated the regulatory effects of fecal microbiota transplantation (FMT) on gut microbiota and host metabolism in weaned Tibetan piglets by integrating 16S rRNA sequencing and metabolomics, with experimental groups including a basal diet (Nor), lincomycin-supplemented (Ant), and FMT-supplemented (Fec) interventions. FMT significantly enhanced gut microbiota alpha diversity (Shannon index), enriching beneficial genera (e.g., Lactobacillus, Prevotella) and functional taxa (e.g., Eubacterium hallii group) to establish a core microbiota dominated by short-chain fatty acid producers and fiber-degrading bacteria, while antibiotics reduced Firmicutes abundance (p < 0.05) and promoted Proteobacteria proliferation. Metabolically, FMT activated tryptophan pathways (e.g., anti-inflammatory 5-hydroxyindole) and bile secretion (ko04976), whereas antibiotics suppressed amino acid metabolism (e.g., N-acetylglycine) and triggered oxidative stress (MAPK signaling). Notably, Streptococcus exhibited dual metabolic roles, positively correlating with phytoestrogens (R-equol) and negatively with biogenic amines (tyramine), highlighting its niche-specific regulatory potential. By reconstructing functional microbiota (e.g., Christensenellaceae) and metabolic networks (tryptophan/riboflavin pathways), FMT achieved comparable growth performance to antibiotics while mitigating dysbiosis and metabolic disturbances. These findings elucidate FMT’s mechanism in alleviating weaning stress through targeted enrichment of fiber-degrading and anti-inflammatory microbiota, coupled with metabolic synergy, thereby validating its feasibility as a non-antibiotic strategy and providing a theoretical framework for precision gut microbiota modulation in sustainable livestock production.